Axiology of science in Islamic perspective - Azizah, Nurul; Anwar, Rosyida Nurul (IAIN Salatiga, 2021)
The history of the development of science is inseparable from the history of thedevelopment of the philosophy of science, the philosophy of science referred to here is the truth system of science as a result of radical, systematic and universal thinking. One of the aims of this study on the usefulness of science (axiology) is to provide support for the process of advancing the science of da'wah among other sciences. The research method in this article is qualitative research with library research. Library research through library research based on literature, namely the main source in the form of library data in the form of books, manuscripts, books, and other sources in the form of other documentation. There is no difference or perspective on the axiology of science in the Islamic perspective. The axiology of science in an Islamic perspective is based on the values of the Qur'an and hadith. There are three branches of axiology of science in the Islamic perspective, namely: ethics, aesthetics and morals.